The sacred embrace of Jesus and Mary the sexual mystery at the heart of the Christian tradition - Leloup, Jean-Yves; Rowe, Joseph (Rochester, Vermont Inner Traditions, 2006)
An examination of how the teachings of Jesus reveal the essential role of sexuality in spiritual growth and transformation • Shows that Jesus did not come to redeem humanity from the life of the flesh, but to honor it as a spiritual path • Uses Hebrew, gnostic, and early Christian source texts to reveal the true context of the words attributed to Jesus • Explores the spiritual and physical relationship shared by Jesus and Mary Magdalene Of all the major religions, Christianity is the only one that has utterly rejected sexuality as one of the many paths that can lead to enlightenment and salvation. But if Jesus was indeed “the Word made flesh” and serious consideration is given to the mystery of his Incarnation, is it reasonable that physical love would have been prohibited to him? Drawing from the canonical and apocryphal gospels, the Hebrew esoteric tradition, and gnosticism, Jean-Yves Leloup shows that Jesus did not come to save humanity from the life of the flesh but to save the life of the flesh so that it would truly transfigure all people. Leloup explains that when Saint Paul said it was good to be without women, he did not cite any words of Jesus in support of this contention. In fact, Paul’s statement utterly contradicts the words of God in Genesis: “It is not good that man should be alone.” Leloup argues that the elimination of the divine feminine and sacred sexuality set in motion by Paul’s words does not reflect the true teachings of Christ, and that the transformation of Jesus into a celibate is the true heresy. His research restores Christ’s true human sexuality and shows it to be a vital part of humanity’s spirituality. Leloup contends that by understanding the sacred nature of the embrace shared by man and woman as a true reflection of humanity made in God’s image, Christianity can again become the powerful path of transfiguration Christ intended.
1. The controversy regarding Mary Magdalene : questions and answers -- 2. A philosophical wonder -- 3. The metamorphoses of the libido -- 4. Docetism -- 5. Kai o Logos Sarx Egeneto : "and the Word was made flesh" -- 6. The sacred embrace according to the Gospel of Philip -- 7. The sacred encounter : the numinous -- 8. The sexuality of Jesus Christ : history, exegesis, theology -- Epilogue : a confession of faith.
Includes bibliographical references (pages 147-150)
"Originally published in French under the title Tout est pur pour celui qui est pur : Jesus, Marie-Madeleine, l'Incarnation by Albin Michel, Paris."--Title page verso.
Keywords: Mary Magdalene -- Saint -- Miscellanea; Jesus Christ -- Miscellanea